Impact Of Tax Appeal Tribunal on Tax Yield in Nigeria - AKINBOBOYE, Gbenga Olanrewaju; OGUNRINDE, Olufemi Philip; FABIYI, Folukemi Catherine (Eastasouth Institute, 2026)
The Tax Appeal Tribunal (TAT) was established in Nigeria with the intention of improving compliance and increasing tax yield by offering a specialized system for addressing disputes between taxpayers and tax officials. The study therefore examines how the Tax Appeal Tribunal (TAT) has affected Nigeria's tax revenue between 2010 and 2023. The TAT was created to speed up the resolution of tax disputes and enhance compliance, but its impact on revenue performance is still poorly understood. The study used secondary data from the Federal Inland Revenue Service, Central Bank of Nigeria, National Bureau of Statistics, and tribunal case records. and employed descriptive statistics, diagnostic tests, correlation analysis, and pooled least squares regression for data analysis The regression result showed that while extended resolution times had a significant negative impact on tax yield, tribunal cases that were resolved had a positive and significant impact. The results showed notable differences in tribunal activity and tax yield, and diagnostic tests validated the reliability of the data. According to correlation analysis, tax yield was negatively correlated with resolution time but strongly positively correlated with both operational zones and cases resolved. Although they had a favorable relationship, operational zones were not statistically significant. The findings show that the tribunal's fiscal impact is driven by institutional efficiency rather than simple expansion. By establishing an empirical connection between tribunal performance and national revenue, the study adds to the body of literature. The study suggests establishing performance goals, minimizing settlement delays, and providing sufficient resources for tribunal zones in order to improve fiscal sustainability.